(untitled) (gjstudies, 2018)
This paper presents a novel, cross-disciplinary investigation into the complexrelationship between regulatory oversight mechanisms and auditor independence,moving beyond traditional compliance-based frameworks. We introduce a dynamic,multi-agent simulation model that conceptualizes the audit ecosystem as a complexadaptive system, where regulators, audit firms, corporate clients, and investorsinteract in non-linear ways. Our methodology uniquely applies principles frombehavioral economics, institutional theory, and network science to model how different oversight structures—ranging from strict punitive regimes to collaborative,principles-based approaches—affect not just the observable compliance of auditors,but their underlying cognitive and institutional independence. We define independence across three novel dimensions: cognitive insulation from client pressure,structural insulation from economic dependencies, and reputational insulation frommarket perceptions. The simulation, parameterized with data from regulatory enforcement actions and audit firm disclosures over a ten-year period, reveals counterintuitive findings. Contrary to conventional wisdom, we find that excessivelyrigid and punitive oversight can, under certain network conditions, create perverseincentives that erode genuine independence by fostering a ’checklist mentality’ anddriving problematic auditor-client relationships underground. Conversely, oversightsystems that incorporate transparency mechanisms, peer review networks, and dynamic risk-based targeting promote more robust and resilient independence. Ourresults demonstrate that the efficacy of a regulatory mechanism is not intrinsic butis contingent on the density and topology of the professional network in which it isdeployed. This research contributes an original theoretical framework and methodological approach for evaluating audit regulation, offering evidence-based insightsfor designing oversight systems that genuinely fortify the bedrock of audit quality.